Regeneration of rice somaclons tolerant to high level of abscisic acid and their characterization via RAPD markers - Adel Elshafei; Mohamed Barakat; Sanaa Milad; Sabry Khattab; Muhammad Al-mutlaq (Bulletin of the National Research Centre, 2019)
Abstract Background The main objectives of this study were to compare two in vitro selection procedures for developing drought-tolerant cell lines from rice cultivars, regenerate plants from the selected cells, and use the random amplified polymorphic DNA (RAPD) method for genetic characterization of somaclons. Callus was derived from mature embryo cultures of tow Egyptian rice cultivars, Sakha 102 and Giza 178. Results The direct in vitro selection method indicated that the callus weight of the two cultivars was significantly decreased in response to increasing ABA concentrations. The shoot formation revealed significant differences among ABA concentrations and highly significant for interaction between rice cultivars and ABA concentrations. The percentage of shoot formation either increased or decreased with increasing ABA levels in rice cultivars. However, Giza 178 cultivar was slightly stable for shoot formation than the cultivar Sakha 102. The obtained results for stepwise selection method indicated also that the shoot formation was obtained till 6 mg/L ABA. The results of the RAPD analysis indicated that the rice cultivars and their somaclons were classified into tow clusters. The polymorphic information content (PIC) per primer ranged from 0.715 to 0.906 with an average of 0.860. The results of UPGMA clustering were consistent with those of the PCoA. Conclusions The percentage for Sakha 102 was 10.8, 7.7, and 2.2% on 2, 4, and 6 mg/L ABA, respectively, and was 16.4, 10.0, and 3.4% for Giza 178 cultivar, at the ABA concentrations of 2, 4, and 6 mg/L, respectively. The genetic similarity among the fifteen genotypes ranged from 0.30 to 0.82. Rice cultivars and their somaclons were classified into five clusters.